Antidiabetic and Antioxidant Activity of Dregea volubilis Fruit in Streptozotocin-Induced Diabetic Rats - Biswas, Moulisha; Bhattacharya, Sanjib; K. Karan, Tarun; Kar, Biswakanth; Suresh Kumar, Rb; K. Ghosh, Ashoke; K. Haldar, Pallab (Asian Journal of Chemistry, 2011)
Present study evaluated antidiabetic and antioxidant effect of petroleum ether extract of Dregea volubilis fruit in Wistar rats. Hyperglycemia was induced in rats by single intraperitonial injection of streptozotocin (STZ, 65 mg/kg body weight). After 3 days, streptozotocin induction, the hyperglycemic rats were treated with petroleum ether extract of Dregea volubilis orally at 100 and 200 mg/kg body weight daily for 15 days. Glibenclamide (0.5 mg/kg, orally) was used as reference drug. The fasting blood glucose levels were measured on every 5th day during the 15 days treatment. Serum and liver biochemical parameters were estimated. petroleum ether extract of Dregea volubilis significantly (p < 0.001) and dose dependently normalized blood glucose levels as compared to that of streptozotocin control. Serum and liver biochemical parameters were significantly (p < 0.001) restored towards normal in petroleum ether extract of Dregea volubilis treated rats as compared to streptozotocin control. Present study infers that Dregea volubilis fruit demonstrated remarkable antidiabetic and antioxidant activity in streptozotocininduced diabetic rats.